2020
DOI: 10.4018/ijictrame.2020070103
|View full text |Cite
|
Sign up to set email alerts
|

Improving Education Delivery in a Technical University in Ghana Through Mobile Learning Technology

Abstract: Although in Accra Technical University (ATU), Ghana there exists a traditional face-to-face (F2F) mode of education already in place, the implementation of mobile learning (m-learning) through ICT in education will solve problems such as small classroom size, inappropriate time schedule for lectures, and provision technological resources needed to run successful classroom education. In order to validate successful implementation of m-learning in ATU, this paper employed a questionnaire research instrument with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In this process, the participants also suggested that there was need for a supportive Policy that would support growth and development of the ICT infrastructure ranging from classrooms, laboratories, recording studios, internet/network/connectivity and affordable electric power. This is supported by Asabere et al, (2017) where he emphasized that the criteria for designing an ICT enabled model for either a class or classroom should involve analysis of ICT education Policy, its status, education goal, the use of ICT in education goals, and its integration in the teaching and learning process. Hence, the need for an ICT Policy brief to ensure that the model effectively supports active teaching and learning in TTIs.…”
Section: Generation Of Model Principles For Active Learning Process A...mentioning
confidence: 99%
“…In this process, the participants also suggested that there was need for a supportive Policy that would support growth and development of the ICT infrastructure ranging from classrooms, laboratories, recording studios, internet/network/connectivity and affordable electric power. This is supported by Asabere et al, (2017) where he emphasized that the criteria for designing an ICT enabled model for either a class or classroom should involve analysis of ICT education Policy, its status, education goal, the use of ICT in education goals, and its integration in the teaching and learning process. Hence, the need for an ICT Policy brief to ensure that the model effectively supports active teaching and learning in TTIs.…”
Section: Generation Of Model Principles For Active Learning Process A...mentioning
confidence: 99%
“…In many universities, the infrastructure for technology related artefacts that support BL are non-existent. ICT tools and equipment like computer laboratories, projectors, lecture workstations, video conferencing facilities, stable and reliable internet connectivity are woefully inadequate (Asabere, Togo, Acakpovi, Torby & Ampadu, 2017). Nonetheless, if these facilities are put in place, there is potential to see universities adopt and implement BL strategies.…”
Section: Blended Learning Adoption In Ghanamentioning
confidence: 99%
“…Some of these universities are implementing BL while others are at various stages of BL adoption (Bervell & Umar, 2020;Bervell & Arkorful, 2020;Budu et al, 2018;Asabere & Enguah, 2012;Asunka, 2018;Graham et al, 2013). According to Asabere et al (2017), the pace of adoption of BL in Ghanaian universities has been slow and this is as a result of challenges to ICT adoption, including, but not limited to, "inappropriate physical environment and ICT infrastructure, unsuitable course content and instructional programs, unsatisfactory number of computers to be used by lecturers and students, inadequate hardware/software, the unavailability of technical and appropriate administrative support and absence of fundamental knowledge/skills for ICT as well as knowledge/skills for ICT integration in education" (Tsapali et al, 2021;Asabere et al, 2017). The above situation presents an unsuitable educational environment for effective BL implementation (Amponsah et al, 2021).…”
Section: Blended Learning In the Ghanaian Education Contextmentioning
confidence: 99%